PKCα Is Recruited to Staphylococcus aureus-Containing Phagosomes and Impairs Bacterial Replication by Inhibition of Autophagy - Gauron, Maria Celeste; Newton, Alexandra C.; Colombo, María Isabel (Frontiers in Immunology, 2021)
Hijacking the autophagic machinery is a key mechanism through which invasive pathogens such as Staphylococcus aureus replicate in their host cells. We have previously demonstrated that the bacteria replicate in phagosomes labeled with the autophagic protein LC3, before escaping to the cytoplasm. Here, we show that the Ca2+-dependent PKCα binds to S. aureus-containing phagosomes and that α-hemolysin, secreted by S. aureus, promotes this recruitment of PKCα to phagosomal membranes. Interestingly, the presence of PKCα prevents the association of the autophagic protein LC3. Live cell imaging experiments using the PKC activity reporter CKAR reveal that treatment of cells with S. aureus culture supernatants containing staphylococcal secreted factors transiently activates PKC. Functional studies reveal that overexpression of PKCα causes a marked inhibition of bacterial replication. Taken together, our data identify enhancing PKCα activity as a potential approach to inhibit S. aureus replication in mammalian cells.